Methicillin-Resistant Staphylococcus aureus Colonization among Medical Residents - Pascale Trépanier; Claude Tremblay; Annie Ruest (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Medical residents may be at risk of becoming colonized by methicillin-resistant Staphylococcus aureus (MRSA) during their training. The occupational risk of this specific population is unknown. Furthermore, there are no data regarding MRSA colonization among health care professionals in Quebec.